2020
DOI: 10.2495/susi200111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wall Support Conditions on Seismic Response of Ground-Supported Reinforced Concrete Containment Tanks

Abstract: Concrete liquid storage tanks are commonly used in regions that may be highly seismic, for the storage of water, petroleum products and other chemicals. In some cases, such as for liquefied natural gas (LNG) tanks, a secondary concrete containment is designed for external protection, ignoring any direct contact or interaction with the inner storage liquid by creating a gap, as another inner tank is used to hold the liquid. Typical secondary containment tanks for LNG are circular, upright concrete tanks, with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Lee et al [28] constructed the concrete outer tank with a gross of 1300 m 3 with the support from Korea Gas Corporation, and obtained its vibration frequencies and mode shapes by sledgehammer impact tests. Sharari et al [29] conducted time history simulations of a prestressed RC outer tank of diameter 41 m subjected to seismic excitation. It was found that large shear forces and bending moments occurred in the tank base, while tensile cracks were predicted around the tank wall-roof junction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [28] constructed the concrete outer tank with a gross of 1300 m 3 with the support from Korea Gas Corporation, and obtained its vibration frequencies and mode shapes by sledgehammer impact tests. Sharari et al [29] conducted time history simulations of a prestressed RC outer tank of diameter 41 m subjected to seismic excitation. It was found that large shear forces and bending moments occurred in the tank base, while tensile cracks were predicted around the tank wall-roof junction.…”
Section: Introductionmentioning
confidence: 99%
“…Sharari et al. [ 29 ] conducted time history simulations of a prestressed RC outer tank of diameter 41 m subjected to seismic excitation. It was found that large shear forces and bending moments occurred in the tank base, while tensile cracks were predicted around the tank wall‐roof junction.…”
Section: Introductionmentioning
confidence: 99%